Pelatihan Kerajinan Tangan Gantungan Pot (Macrame) Sebagai Upaya Pemberdayaan Generasi Muda Guna Meningkatkan Ekonomi Keluarga Di Masa Pandemi Covid-19 - Jesi Alexander Alim; Aretha Putri; Mhd Fadli Waluyo; Rio Fandy Sitepu; Akmal Lahia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The Covid-19 pandemic has changed the order of people's lives massively, as in Indonesia, which experienced an economic downturn as evidenced by the closure of the business industry and the termination of employment relations (layoffs), resulting in many families losing their sources of income and economy. As a result, people had to be able to think creatively in utilizing all opportunities in this pandemic situation to find a way out, such as responding to changes in the behavior of people who significantly have new hobbies, namely planting and collecting ornamental plants in the yard. Problems arise when some people have limited land and do not even have a yard, so they have difficulty placing their collection of plants, and because of that, they have to hang the plant. This issue is what can be used by the community to open business opportunities. Training in making pot hangers with macrame techniques is present in response to the problem by empowering the community, especially young people. Therefore, with this training, young people of productive age will be able to independently producing, open new business opportunities, and make a passive income to improve the family economy in the pandemic period.